Farewell to the party of Lincoln : Black politics in the age of FDR - Weiss, Nancy J. (Nancy Joan), 1944- (Princeton University Press, 1983)
This book examines a remarkable political phenomenon -- the dramatic shift of black voters from the Republican to the Democratic party in the 1930s, a shift all the more striking in light of the Democrats' indifference to racial concerns. Nancy J. Weiss shows that blacks became Democrats in response to the economic benefits of the New Deal and that they voted for Franklin Roosevelt in spite of the New Deal's lack of a substantive record on race. - Jacket flap.